Optimal high‐level control of building HVAC system under variable price framework using partially linear model. Issue 2 (2nd May 2021) - He, Yiliu; Zhong, Haiwang; Tan, Zhenfei; Zhan, Jiayue
Abstract: As typical thermostatic loads, heating, ventilation, and air conditioning (HVAC) systems possess high flexibility due to buildings' thermal inertia. It is beneficial to coordinate HVAC loads with power grid operations. However, it is difficult to model the HVAC loads of realistic buildings. A partially linear model is proposed to capture the electrothermal characteristics of building HVAC loads. The proposed model combines the explainability of a physically based model and the fitting capability of a data‐driven model. The model retains linearity regarding mapping the control variables to the HVAC load and thus is compatible with existing studies based on the assumption of a succinct HVAC load model. Based on the proposed model, an optimal control strategy is developed to minimize the HVAC operational cost while considering comfort requirements of occupants. EnergyPlus is used as the building simulation engine to validate the proposed model and optimal control strategy.